Key-drivers in hotel and environmental management: a comparative analysis in Malaysia - Kasim, Azilah; Scarlat, Cezar; Rashid Radha, Jasmine Zea Raziah Radha (Inderscience Publishers, 2008)
In tourism, the environment is a core business product.Since hotels occupy a central place in the tourism industry and its development does impact upon the environment considerably, it is believed that hotels should be more proactive in their managerial response concerning environmental performance.Using interview data, this study compares the environmental management practices among hotels operating in Penang and Langkawi, Malaysia.The results have shown that although hotel companies in both destinations are concerned with environmental management issues, many are not proactive enough in their responses and prefer to only take management initiatives that have considerable financial benefits for their business.Focus has been mainly on cost-cutting management measures such as minimising energy use and water conservation as this contributes directly toward a hotel|s profitability. In both cases, business refuses to take sole ownership on environmental management.Instead, the government and society are expected to play a leading role before business can be expected to emulate.